AI in Elderly Care: Understanding the Implications for Independence and Social Interaction - Gottschlich, Daniela; Saadati, Nadereh; Saadati, Seyed Alireza; Şahin, Ayşe (AI and Tech in Behavioral and Social Sciences, 2024)
This study aims to explore the implications of AI in elderly care, specifically its impact on enhancing independence and social interaction among the elderly. Additionally, it seeks to identify and analyze the ethical and privacy concerns, technological challenges, and the potential for personalization and customization in AI applications in elderly care settings. Employing a qualitative research design, this study collected data through semi-structured interviews with a purposively sampled cohort of 17 participants, including healthcare professionals specializing in geriatric care, caregivers using AI tools, and elderly individuals interacting with AI technologies. Thematic analysis was utilized to identify and interpret patterns within the data, leading to the delineation of five main themes and their respective categories and concepts. The analysis revealed five major themes: Impact on Independence, Enhancements in Social Interaction, Ethical and Privacy Concerns, Technological Challenges and Solutions, and Personalization and Customization in AI. Each theme encompasses several categories detailing specific implications of AI in elderly care, from supporting physical and cognitive autonomy to addressing concerns over data security and the potential for technology-driven bias. AI holds significant promise for improving elderly care by supporting independence and facilitating social interactions, yet its integration must be approached with caution to address ethical and privacy concerns. The successful implementation of AI in elderly care requires a balanced, human-centric approach that leverages technological advancements while ensuring they align with the needs and values of the elderly population.